Comparação de dois protocolos de analgesia para tratamento de emergências ortopédicas pediátricas - Barcelos, Andrea Lucia Machado (2012)
AIM : To compare the efficacy of the intravenous administration of two analgesics (morphine or ketamine) for reduction of fractures or dislocations in children.METHODS : Randomized and controlled study conducted in the emergency department of a university hospital. Patients between 3 years to 14 years and 6 months old presenting dislocation or bone fracture requiring closed reduction were included. A previous sedation was provide with midazolam and analgesia was performed in a random way: IV ketamine or IV morphine. The groups were then compared to time required to start the intervention, the duration of the reduction and immobilization, the child's cooperation during the procedure, to the satisfaction of parents and orthopedic and adverse reactions.RESULTS : Twenty-five children were included. Demographic data, type of injury and pain scores before procedure was similar in both groups. The duration of the procedure was significantly lower in the morphine group compared to the ketamine group (median 3 versus 5 minutes; < p 0.027). The median pain score of the child after the procedure was 2 in both groups. Parents (guardians children) as well as orthopedic surgeons were very satisfied in both groups (p>0,3 and >0,2). One patient in the ketamine group and 3 in the morphine group presented lower saturation with rapid reversion (p>0,2).CONCLUSION : The results support the efficacy of ketamine as compared with standard analgesics such as morphine, in facilitating the reduction of dislocations or fractures in pediatric emergency with respect to pain relief and anxiety and parental satisfaction and orthopedists.